Reversible Zn/polymer heterogeneous anode - Xiong, Lingyun; Fu, Hao; Yang, Kai; Kim, Ji Young; Ren, Ren; Lee, Joong Kee; Yang, Woochul; Liu, Guicheng (Wiley, 2023)
Commercialization of Zn-metal anodes with low cost and high theoretical capacity is hindered by the poor reversibility caused by dendrites growth, side reactions, and the slow Zn2+-transport and reaction kinetics. Herein, a reversible heterogeneous electrode of Zn-nanocrystallites/polyvinyl-phosphonic acrylamide (Zn/PPAm) with fast electrochemical kinetics is designed for the first time: phosphonic acid groups with strong polarity and chelation effect ensure structural reversibility and stability of the three-dimensional Zn-storage-host PPAm network and the Zn/PPAm hybrid; hydrophobic carbon chains suppress side reactions such as hydrogen evolution and corrosion; weak electron-donating amide groups constitute Zn2+-transport channels and promote "desolvation" and "solvation" effects of Zn2+ by dragging the PPAm network on the Zn-metal surface to compress/stretch during Zn plating/stripping, respectively; and the heterostructure and Zn nanocrystallites suppress dendrite growth and enhance electrochemical reactivity, respectively. Thus, the Zn/PPAm electrode shows cycle reversibility of over 6000 h with a hysteresis voltage as low as 31 mV in symmetrical cells and excellent durability and flexibility in fiber-shaped batteries.